E-Planning and E-Budgeting Implementation: A Qualitative Study in Lampung Province - Gamayuni, Rindu Rika; Agusta, Elia (FEB - Universitas Lampung, 2019)
This is a qualitative research aimed to observe the implementation of e-planning and e-budgeting in Lampung Province through an empirical study that investigates readiness of using technology in governmental activity. This study based on interview collected from a total of 12 local government officials that located in Bandar Lampung, Metro, Pringsewu, Pesawaran, and Lampung Selatan using Nvivo 12 as analysis tool. The findings show Lampung Province is ready to implement e-planning and e-budgeting, e-planning and e-budgeting in Lampung Province have been implemented for more than 10 years, improvement in education, human resources, and fund are necessary, then good corporate governance principles and society participation performs better during the implementation. This research is limited to six locations in Lampung Province only, the timeline of the observation does not significantly cover the whole process of e-planning and e-budgeting, and solely focus on e-planning and e-budgeting, does not observe the whole types of e-government just like e-procurement, e-audit, e-catalog, e-payment, e-controlling, and e-health.